P Alterations in Plasma Proteome Pattern and Oxidative Stress in Patients with Type 2 Diabetes - Kheirodin , Razie; Jafari Sani , Moslem; Goodarzi, Mohamad Taghi (Shahroud Journal of Medical Sciences, 2021)
Background: Free radical production, changes in the proteome, and lipid peroxidation are the consequences of hyperglycemia in diabetes. This study aimed to examine the changes in plasma proteome along with oxidative status in type 2 diabetes. Methods: Thirty type 2 diabetic patients and 25 healthy subjects participated in this cross-sectional study. Fasting blood sugar, glycated hemoglobin (HbA1c), and lipid profile was measured in all subjects. To measure oxidative stress parameters, malondialdehyde (MDA) and total antioxidant capacity (TAC) were assayed. Plasma proteome pattern was determined using two-dimensional gel electrophoresis. Visual analysis of gels was performed using software (Image Master). Results: MDA level was higher in the diabetic group compared to the healthy group 4.10 (± 0.57) vs. 3.2 (± 0.10) nmol/ml, Pvalue<0.01). TAC reduced in diabetic patients 17.85 (± 1.2) vs. 38.60 (± 2.4) mmol/ml, Pvalue=0.01). Some changes were observed in the 2-D gel electrophoresis pattern in diabetic patients comparing to those of the healthy group. Conclusions: The results indicated the presence of oxidative stress in type 2 diabetes patients. Also, different proteome patterns showed the presence of different or modified proteins in diabetic patients that can be due to changes in the glycation of proteins or may be induced as a response to oxidative stress. Keywords: Diabetes, Plasma proteome, Malondialdehyde, Total antioxidant, Two-dimensional electrophoresis.